Endocannabinoid regulation of inward rectifier potassium (Kir) channels - Mayar, Sultan; Borbuliak, Mariia; Zoumpoulakis, Andreas; Bouceba, Tahar; Labonté, Madeleine M.; Ahrari, Ameneh; Sinniah, Niveny; Memarpoor-Yazdi, Mina; Vénien-Bryan, Catherine; Tieleman, D. Peter; D’Avanzo, Nazzareno (Frontiers in Pharmacology, 2024)
The inward rectifier potassium channel Kir2.1 (KCNJ2) is an important regulator of resting membrane potential in both excitable and non-excitable cells. The functions of Kir2.1 channels are dependent on their lipid environment, including the availability of PI(4,5)P2, secondary anionic lipids, cholesterol and long-chain fatty acids acyl coenzyme A (LC-CoA). Endocannabinoids are a class of lipids that are naturally expressed in a variety of cells, including cardiac, neuronal, and immune cells.While these lipids are identified as ligands for cannabinoid receptors (CBRs), there is a growing body of evidence that they can directly regulate the function of numerous ion channels independently of CBRs.Here we examine the effects of a panel of endocannabinoids on Kir2.1 function and demonstrate that a subset of endocannabinoids can alter Kir2.1 conductance to varying degrees independently of CBRs.Using computational and SPR analysis, endocannabinoid regulation of Kir2.1 channels appears to be the result of altered membrane properties, rather than through direct protein-lipid interactions. Furthermore, differences in endocannabinoid effects on Kir4.1 and Kir7.1 channels, indicating that endocannabinoid regulation is not conserved among Kir family members. These findings may have broader implications on the function of cardiac, neuronal and/or immune cells.